2022
DOI: 10.3389/fphar.2022.974271
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of sodium bicarbonate infusion on mortality for elderly septic patients with acute metabolic acidosis

Abstract: Objective: This study aimed to explore the effectiveness of sodium bicarbonate (SB) infusion on mortality in elderly septic patients with acute metabolic acidosis (MA) and in other subgroups.Methods: Retrospective analysis of a large ICU database (MIMIC-IV) was performed. Elderly septic patients with acute MA were identified from MIMIC-IV. Propensity score analysis (PSA) was performed to explain for the baseline differences in the probability to receive SB or not. The marginal structural Cox model (MSCM) was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… 19 In a single centre retrospective study using the open access MIMIC-3 database, 869 patients older than 60 years old with sepsis and moderate metabolic acidosis (pH≤7.3 and bicarbonataemia less than 20 mmol/L) were evaluated according to whether they received sodium bicarbonate or not within 48 hours after the ICU admission. 12 Both ICU and hospital mortality were significantly reduced in the subgroup of patients with moderate metabolic acidemia (7.2<pH<7.3) treated with sodium bicarbonate. Using the same MIMIC-3 database and moderate acidemia (pH<7.30), Wang et al suggested that sodium bicarbonate was not associated with survival and that sodium bicarbonate might be associated with worsening organ failure score in a subset of patients with unchanged or deteriorating haemodynamics before sodium bicarbonate infusion.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“… 19 In a single centre retrospective study using the open access MIMIC-3 database, 869 patients older than 60 years old with sepsis and moderate metabolic acidosis (pH≤7.3 and bicarbonataemia less than 20 mmol/L) were evaluated according to whether they received sodium bicarbonate or not within 48 hours after the ICU admission. 12 Both ICU and hospital mortality were significantly reduced in the subgroup of patients with moderate metabolic acidemia (7.2<pH<7.3) treated with sodium bicarbonate. Using the same MIMIC-3 database and moderate acidemia (pH<7.30), Wang et al suggested that sodium bicarbonate was not associated with survival and that sodium bicarbonate might be associated with worsening organ failure score in a subset of patients with unchanged or deteriorating haemodynamics before sodium bicarbonate infusion.…”
Section: Discussionmentioning
confidence: 92%
“…After adjusting for confounders, sodium bicarbonate was associated with higher mean arterial pressure at 6 hours among the patients with vasopressors dependency but not with mortality 19. In a single centre retrospective study using the open access MIMIC-3 database, 869 patients older than 60 years old with sepsis and moderate metabolic acidosis (pH≤7.3 and bicarbonataemia less than 20 mmol/L) were evaluated according to whether they received sodium bicarbonate or not within 48 hours after the ICU admission 12. Both ICU and hospital mortality were significantly reduced in the subgroup of patients with moderate metabolic acidemia (7.2<pH<7.3) treated with sodium bicarbonate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of metabolic acidosis, as indicated by low HCO3- levels, may reflect tubular interstitial disease and poor renal function, leading to an increased risk of AKI [ 41 ]. Previous retrospective cohort studies have confirmed this association, and the use of sodium bicarbonate infusion has been explored as a potential intervention to improve kidney and survival outcomes [ 25 , 42 ].…”
Section: Discussionmentioning
confidence: 93%